The Lived Experiences of Parents of Traditional Low-income Households in the Shift from Modular to Blended Learning: A Phenomenological Study in the Philippines during the COVID-19 Pandemic - Lumba, David Neil Joseph V.; Abella, Fiorella Matilda; Andaya III, Robert; Bea, Warren Victor; Pel, Jillian Maristela; Tanchuling, Neville Antonio (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The COVID-19 pandemic necessitated a shift in educational modalities, notably from modular to blended learning, creating unique challenges for low-income households in the Philip-pines. This study examines the lived experiences of 11 Baran-gay Manggahan, Pasig City parents during this transition. A qualitative phenomenological approach was utilized to capture the complexities of their adaptation, focusing on access to technology, economic pressures, and the home learning envi-ronment. Data were collected through in-depth, semi-structured interviews and analyzed using thematic analysis. Participants were purposively selected to represent tradi-tional low-income households with school-aged children en-gaged in blended learning. The findings revealed significant barriers, including limited access to devices and internet con-nectivity, compounded by financial instability. These con-straints strained parents' abilities to support their children’s education, although many adopted strategies like promoting independence, leveraging community resources, and reorganiz-ing household routines. Despite the challenges, parents gener-ally perceived blended learning as an improvement over modu-lar learning due to increased teacher interaction and enhanced learning opportunities. However, issues such as inconsistent schedules and the financial burden of the hybrid format persisted. The study underscores the digi-tal divide as a critical factor exacerbating educational inequi-ties, highlighting the need for systemic interventions. In addi-tion to this, targeted efforts to improve digital access, provide economic support, and enhance parent-teacher collaboration are vital for fostering inclusive and effective education. These findings contribute to policy discussions on addressing so-cio-economic disparities in education, particularly in post-pandemic recovery planning.